2018
DOI: 10.1002/adsc.201801030
|View full text |Cite
|
Sign up to set email alerts
|

Ca(II)‐Mediated Regioselective One‐pot Sequential Annulation of Acyclic compounds to Polycyclic Fluorenopyrans

Abstract: Herein we report a facile synthesis of tetracyclic fluorenopyrans from simple acyclic reactants, propargyl alcohols and 3-methylpentane-2,4-dione under calcium catalysis. This one-pot, 3-component reaction proceeds through a sequential allene formation, Friedel-Crafts cyclization/cycloisomerization, intramolecular aldol reaction, Claisen rearrangement, and 6-endo dig cyclization to result in the formation of fluorenopyrans (indeno[2,1-g]chromenes). This strategy was further used in the synthesis of 3-iodofluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…To find out the suitable reaction conditions of the ring‐rearrangement reaction, we have selected 5,11‐dimethyl‐2,2,4,6,6‐pentaphenyl‐2,6‐dihydroindeno[2,1‐ g ] chromene 1a as the model substrate, which was synthesized using a reported method . Among the various reaction conditions studied, we found that when 1a was heated at 110 °C with 20 mol‐% of p TsOH the reaction gave the best yield, Under these conditions, compound 1a underwent an irreversible ring‐rearrangement via ring‐opening‐cyclization to furnish 2‐(1,1‐diphenyl‐1 H ‐inden‐3‐yl)‐1,4‐dimethyl‐9,9‐diphenyl‐9 H ‐fluoren‐3‐ol 2a in nearly quantitative yield after 90 minutes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To find out the suitable reaction conditions of the ring‐rearrangement reaction, we have selected 5,11‐dimethyl‐2,2,4,6,6‐pentaphenyl‐2,6‐dihydroindeno[2,1‐ g ] chromene 1a as the model substrate, which was synthesized using a reported method . Among the various reaction conditions studied, we found that when 1a was heated at 110 °C with 20 mol‐% of p TsOH the reaction gave the best yield, Under these conditions, compound 1a underwent an irreversible ring‐rearrangement via ring‐opening‐cyclization to furnish 2‐(1,1‐diphenyl‐1 H ‐inden‐3‐yl)‐1,4‐dimethyl‐9,9‐diphenyl‐9 H ‐fluoren‐3‐ol 2a in nearly quantitative yield after 90 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…Then a general method was reported by us that a naphthopyran [ IE ] can be effectively rearranged to (inden‐3‐yl)naphthalenol [ IF ] . On the other hand, while we are working on annulation reactions to construct the fluorenopyran 1a , we observed that the addition of trifluoroacetic acid, lead to the formation of an intense brick red colour solution, and this becomes colourless when triethylamine was added (Figure ). This colour changes can be understood based on the ring‐opening of 1a with protonation and ring closure with base (NEt 3 ) as depicted in Figure .…”
Section: Introductionmentioning
confidence: 84%
“…Etherification of 39 with 35 gave the iodocyclization precursor 39′ . Electrophilic iodine promoted 6‐ endo cyclization of 39′ gave 3‐iodo‐fluorenopyrans 40a – 40f in good yields (Scheme ) . Interestingly all these reactions were performed in one‐pot, and in this protocol 7 new bonds were formed.…”
Section: Oxygen‐containing Heterocyclic Iodidesmentioning
confidence: 99%
“…In the past few years, iodocyclization of propargylic systems, particularly propargyl alcohols, has been emerging as one of the potential strategies for the construction of various pre‐functionalized carbo and heterocyclic compounds . Recently, our group has demonstrated a one‐pot synthesis of iodo‐quinolines,[11f], [11h] iodochromenes,[11g] iodo‐fluorenopyrans[12b] though iodocyclization of propargyl alcohols. Further, these strategic advances have led to a general, one‐pot synthesis of 3‐iodo‐carbazoles from indole‐tethered propargyl alcohols (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…[11h] To the best of our knowledge, there is no single report available to access 2‐iodocarbazoles through benzannulation or iodocyclization protocol directly. Our continued investigations in the field of benzannulation reactions form indole to carbazole lead us to disclose herein a highly regioselective, one‐pot, transition metal‐free and first approach of 2‐iodocarbazole synthesis.…”
Section: Introductionmentioning
confidence: 99%